May Measurement Month 2017: an analysis of the blood pressure screening campaign results in Pakistan—South Asia. (24th April 2019) - Ishaq, Mohammad; Memon, Feroz; Beaney, Thomas; Xia, Xin; Kobeissi, Elsa; Poulter, Neil R
Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. May Measurement Month (MMM) is a global initiative aimed at raising awareness of high BP and to act as a temporary solution to the lack of screening programs worldwide. Hypertension is a global health concern for developing countries. In Pakistan, apart from few population-based studies which evaluated the prevalence of hypertension, there is no current nationally representative study (the latest nationwide survey was conducted more than two decades ago). Pakistan Hypertension League, in accordance with the International Society of Hypertension directive under the banner of the May Measurement Month 2017 (MMM17) campaign, carried out a nationwide cross-sectional survey of volunteers aged ≥18 in May 2017 through its 14 regional chapters. Blood pressure measurement recorded through digital apparatus, the definition of hypertension (≥140/90 mmHg or being on BP-lowering treatment) and statistical analysis followed the standard MMM protocol. A total of 5333 individuals were screened during the MMM17 campaign with mean age 45.0 (11.6). Males had a higher rate (66.3%, n = 3536) in those screened than females (33.0%, n = 1757). A total of 55.2% ( n = 2943) people had hypertension. This result shows very high rates of hypertension in Pakistani people. Therefore, there is an urgent need for federal implementation of BP screening as well as awareness programs across the nation.